The Effect of Skills and Motivation on Employee Performance with Innovation as a Moderator at the Regional Research and Development Agency of South Central Timor Regency - Banusu, Mario Randi; Pellokila, Mayantri Christina; Tulle, Carlito D.C.; Manu, Dominicus E. Chr.; Ulus, Meldi E. (AKSIOMA : Jurnal Manajemen, 2026)
Employee performance at BALITBANGDA, South Central Timor Regency, has been a bit of a sticking point despite being key to achieving the organisation’s goals. Previous studies suggest that skills, motivation, and innovation all play a part in shaping staff performance. This study set out to examine how skills and motivation affect employee performance, with innovation tested as a moderating variable. A quantitative approach was used, and because the organisation only had 31 employees, everyone was included in the sample using a saturated sampling technique. Data was gathered through interviews, questionnaires, observations, and documentation, then analysed using SmartPLS 3. The findings showed that both skills and motivation had a significant impact on employee performance, with p-values of 0.000 and 0.003 respectively. Innovation, however, didn’t strengthen the relationship between either skills or motivation and performance, as reflected by p-values of 0.509 and 0.665. The novel bit of this research lies in testing innovation as a moderator. From a theoretical point of view, the findings lend support to existing theories on skills, motivation, innovation, and performance, while also adding fresh empirical evidence to the field of human resource management.